Rancang Bangun Sistem Informasi Akuntansi HPP Berdasarkan Pesanan Pada Usaha Industri Rumahan Manufaktur - Widy Firdha Lestari; Apriani Puti Purfini (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
The purpose of this research to engineering information system accounting HPP on order for cottage industries and the organizational structure. This study using method of development information system the iteration with structured. The results of research in the form of application cost of good sold in accordance with standard and the proposed organizational structure.